NOVEL BENZO CROWN ETHER CAVITAND AND BENZO CROWN ETHER FERROCENYL HOST MOLECULES THAT BIND BIPYRIDINIUM AND SODIUM GUEST CATIONS - Beer, P; Tite, E; Ibbotson, A (1989)
The syntheses, co-ordination, and electrochemistry of novel macrocyclic benzo crown ether (6), (8), and benzo crown ether-ferrocenyl (7) host molecules, each containing four benzo-15-crown-5 moieties and, in the case of (7), eight ferrocenyl redox-active centres, are reported; the new hosts bind bipyridinium and sodium guest cations.